International Education in Australia: The Roller Coaster - Marginson, Simon (International Higher Education, 2012)
Australia's international education industry', a major export sector, slumped in 2010 because of more restrictive migration policy and visa processing, a crackdown on backdoor migration schemes, a high Australian dollar and tardy official response to racist violence affecting international students. A package of reforms in late 2011 freed up visa processing and work experience for graduates but so far industry recovery has been slow and uncertain.